Ulcerated Scrotal Hemangioma in an 18-Month-Old Male Patient: A Case Report and Review of the Literature - Ioannis Patoulias; Konstantinos Farmakis; Christos Kaselas; Dimitrios Patoulias (Case Reports in Urology)
Deep scrotal hemangiomas are rare. Less than 50 case reports have been published. After systematic research of the literature, we found less than 5 cases of ulcerated scrotal hemangioma. The aim of this case report is to illustrate the challenges of scrotal hemangiomas pose and their potential therapies based on the successful surgical treatment of an ulcerated scrotal hemangioma in an 18-month-old male patient.